Prognosis of pacing-dependent patients with cardiovascular implantable electronic devices - Grimm, Wolfram; Erdmann, Barbara; Grimm, Kathrin; Kreutz, Julian; Parahuleva, Mariana (Herzschrittmachertherapie und Elektrophysiologie, 2024)
Background: Data on the prognostic significance of pacing dependency in patients with cardiovascular implantable electronic devices (CIEDs) are sparse. Methods: The prognostic significance of pacing dependency defined as absence of an intrinsic rhythm ≥ 30 bpm was determined in 786 patients with CIEDs at the authors’ institution using univariate and multivariate regression analysis to identify predictors of all-cause mortality. Results: During 49 months median follow-up, death occurred in 63 of 130 patients with pacing dependency compared to 241 of 656 patients without pacing dependency (48% versus 37%, hazard ratio [HR] 1.34; 95% confidence interval [CI]: 1.02–1.78, P = 0.04). Using multivariate regression analysis, predictors of all-cause mortality included age (HR 1.07; 95% CI: 1.05–1.08, P < 0.01), history of atrial fibrillation (HR 1.32, 95% CI: 1.03–1.69, P < 0.01), chronic kidney disease (HR 1.28; 95% CI: 1.00–1.63, P = 0.048) and New York Heart Association (NYHA) class ≥ III (HR 2.00; 95% CI: 1.52–2.62, P < 0.01), but not pacing dependency (HR 1.15; 95% CI: 0.86–1.54, P = 0.35). Conclusions: In contrast to age, atrial fibrillation, chronic kidney disease and heart failure severity as indexed by NYHA functional class III or IV, pacing dependency does not appear to be an independent predictor of all-cause mortality in patients with CIEDs.
CRIS-Team Scopus Importer:2024-02-16
Keywords: Chronic kidney disease; Heart failure; Implantable cardioverter-defibrillator; Pacing dependency; Permanent pacemaker